Synthesis of N-[(dialkylamino)methyl]acrylamides and N-[(dialkylamino)methyl]methacrylamides from Schiff base salts: useful building blocks for smart polymers. Issue 22 (18th May 2018) - Alzahrani, Abdullah; Mirallai, Styliana I.; Chalmers, Benjamin A.; McArdle, Patrick; Aldabbagh, Fawaz
Abstract : Schiff base salts are characterized and form N -amino methylated acrylamides and methacrylamides. Abstract : The traditional thermal Mannich reaction is unsuitable for preparing polymerizable N -methylene amino substituted acrylamides and methacrylamides. Herein we provide a facile multi-gram high yield synthesis of these monomeric precursors to stimuli-responsive polymers by the addition of acrylamides and methacrylamides onto in situ generated or freshly isolated methylene Schiff base (iminium) salts. The X-ray crystal structure of the hydrated iminium salt, 1-(hydroxymethyl)azocan-1-ium chloride and monomer·HCl salt ( N -[(azocan-1-yl)methyl]prop-2-enamide hydrochloride) is described.